STRATEGI INDONESIA DALAM MENANGGULANGI KELEBIHAN KAPASITAS SIARAN (SPILLOVER) MALAYSIA DI KAWASAN PERBATASAN KALIMANTAN TIMUR 2012-2014 - M.Fajar Ma’ruf; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to explain the spillover problems in the border area of Indonesia, especially East Kalimantan which became one of the most alarming areas affected by the spillover of foreign broadcasts. Spillover broadcasts Malaysia is the most dominant of 98% of radio and television frequencies in the East Kalimantan border area in Nunukan, all people on the East Kalimantan border are so used to enjoying Malaysian television broadcasts that it is feared that if it keeps happening it will lead to erosion of the values and spirit of nationalism.This research uses the theory of liberalism in international relations and is supported by the level of state analysis and the concept of national interest. The formulation of all arguments, facts, and theories in this paper uses qualitative research. The focus of this research is the Indonesian Government's strategy to tackle spillover problems in the border area of East KalimantanResearchers have formulated an answer-hypothesis that reveals the fact that since 2003 spillover has been discussed in a forum known as Joint Commitee Communication, until 2014 Indonesia-Malaysia bilateral relationship is increasing. Coupled with the strategy of the Indonesian government to make the border area into the main page of the Unitary Republic of Indonesia. The Joint Committee Communication Forum is held every once a year, in 2012 spillover problems in east kalimantan become the main topic because 98% of Indonesian orbit slots in Nunukan are controlled by Malaysia. After this problem became the government's attention, the agreement between the two countries increased the formulation of cooperation and coordination, so the Joint Committee on Communication forum became an effective bilateral aspect to overcome spillover.Keywords: Spillover, National Interest, Bilateral Relations, Joint Committee on Communication, Influence